Increased pCO2 and temperature reveal ecotypic differences in growth and photosynthetic performance of temperate and Arctic populations of Saccharina latissima - Olischläger, Mark; Íñiguez Moreno, Concepción; Koch, Kristina; Wiencke, Christian; López-Gordillo, Francisco Javier (Springer, 2017)
The previous research demonstrated that warming and ocean acidification (OA) affect the biochemical composition of Arctic (Spitsbergen; SP) and cold-temperate (Helgoland; HL) Saccharina latissima differently, suggesting ecotypic differentiation. This study analyses the responses to different partial pressures of CO2 (380, 800, and 1500 latm pCO2) and temperature levels (SP population: 4, 10  C; HL population: 10, 17  C) on the photophysiology (O2 production, pigment composition, D1-protein content) and carbon assimilation [Rubisco content, carbon concentrating mechanisms (CCMs), growth rate] of both ecotypes. Elevated temperatures stimulated O2 production in both populations, and also led to an increase in pigment content and a deactivation of CCMs, as indicated by 13C isotopic discrimination of algal biomass (ep) in the HL population, which was not observed in SP thalli. In general, pCO2 effects were less pronounced than temperature effects. High pCO2 deactivated CCMs in both populations and produced a decrease in the Rubisco content of HL thalli, while it was unaltered in SP population. As a result, the growth rate of the Arctic ecotype increased at elevated pCO2 and higher temperatures and it remained unchanged in the HL population. Ecotypic differentiation was revealed by a significantly higher O2 production rate and an increase in Chl a, Rubisco, and D1 protein content in SP thalli, but a lower growth rate, in comparison to the HL population. We conclude that both populations differ in their sensitivity to changing temperatures and OA and that the Arctic population is more likely to benefit from the upcoming environmental scenario than its Atlantic counterpart.
Keywords: Algas - Fisiología; Arctic; Carbon Concentrating Mechanisms; Kelp; Ocean Acidification; Photosynthesis; Pigment; Seaweed